Meta-Analysis: The Effect of Lifestyle Interventions on Decreased Postpartum Weight Retention - Fazrina, Gina; Hastuti, Uki Retno Budi; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Postpartum weight retention is the increase in postnatal weight compared to pre-pregnancy weight. This weight gain may persist and increase the long-term prevalence of obesity in women. The application of lifestyle interventions consisting of diet, physical activity, and behavior change interventions is believed to be able to reduce postpartum weight retention. This study aims to determine the effectiveness of lifestyle interventions carried out during pregnancy for reducing postpartum weight retention based on various types of interventions derived from studies that have been conducted. Subjects and Method: The writing of this meta-analysis was based on the PRISMA 2020 flow diagram with population: pregnant women, intervention: lifestyle intervention, comparison: without lifestyle intervention, and outcome: postpartum weight retention. The selected articles are full articles, randomized controlled trials (RCT) issued in 2013 – 2022, and are in English. Selected studies were assessed based on the JBI Critical Appraisal Checklist for RCT and then analyzed using RevMan 5.3. Results: 778 articles were identified from December 2022 to January 2023 and 14 RCT articles were obtained for meta-analysis. The diet subgroup accompanied by a behavior change intervention had the largest effect size (SMD = -0.60, 95% CI -0.86 to -0.33, p<0.001), followed by the diet subgroup accompanied by physical activity and behavior change intervention (SMD = -0.10, CI 95 % -0.14 to -0.06, p < 0.001). Physical activity was found to reduce postpartum weight retention, but not statistically significant. The results of the type of intervention subgroup difference test showed a statistically significant effect (p = 0.001). Conclusion: Diets coupled with behavioral interventions show superior results. Variations in the types of lifestyle interventions carried out during pregnancy can influence the success of interventions for postpartum weight loss. Keywords: Postpartum weight retention, lifestyle intervention, diet, physical activity, meta-analysis. Correspondence:Gina Fazrina. Master’s Program in Public Health, Universitas Sebelas Maret Surakarta, Jl. Ir. Sutami 36A, Central Java 57126, Indonesia. Email: ginafazrina@gmail.com. Mobile: +6281212533833.